Multi Micronutrient Supplement (Mms) Is Effective In Increasing Ferritin Levels In Female Adolescents In Gianyar Regency, Bali Province - Ida Ayu Eka Padmiari; Pande Putu Sri Sugiani (International Journal of Health Engineering and Technology, 2022)
Based on Riskesdas, 2018 shows that the prevalence of anemia in women of childbearing age (WUS) in Indonesia is 23.7% with anemia sufferers aged 5-14 years of 26.8%, anemia sufferers aged 15-24 years of 32.0%, anemia sufferers aged 25- 34 years of 15.1% and anemia sufferers aged 35-44 years of 16.7%. The prevalence of anemia in women of childbearing age (WUS) in Bali based on the 2013 Riskesdas results was 10.8 % . The World Health Organization (WHO) targets to reduce anemia by 50 percent by 2025 in women of reproductive age (WUS) aged 15-49 years. In Bali, research on the prevalence of anemia in adolescents, to the best of the knowledge of the authors, is still very minimal. According to the results of the study showed that 11.4 % of subjects experienced anemia. Subjects with energy and protein intake were in the less category, namely 37.1 % and 50%. The subject's intake of vitamins and micronutrients was still lacking, namely vitamin B2 of 72.9%, zinc 68.6%, iron 92.9%, and folic acid 90% and most of the subjects (68.6%) intake of vitamin C was included in the category good.